Circulating leptin levels in juvenile idiopathic arthritis: a marker of nutritional status?. Issue 1 (17th December 2004) - Perfetto, F; Tarquini, R; Simonini, G; Bindi, G; Mancuso, F; Guiducci, S; Matucci-Cerinic, M; Falcini, F
Abstract : Background: Weight loss is common in juvenile idiopathic arthritis (JIA) and has been positively correlated with an increase in the production of proinflammatory cytokines. Objective: To assess if plasma leptin is a mediator of cytokine dependent decreased food intake during inflammatory diseases and if it is increased in JIA. Methods: Leptin levels were determined in 31 patients with polyarticular disease and in 37 with oligoarticular disease; 32 healthy children served as controls. Results: Patients had significantly reduced body mass index (BMI) compared with controls (17.3 (3) v 19.1 (3) kg/m 2 ; p<0.005). Leptin was significantly lower in patients than controls (8.1 (4.8) v 10.7 (7.3) ng/ml; p = 0.036), but leptin/BMI values were similar. Absolute (8.2 (4.8) v 8 (4.9); p>0.05) and normalised (0.45 (0.24) v 0.47 (0.24); p>0.05) leptin levels were not significantly different between patients with active and inactive disease and between patients with oligoarticular and polyarticular arthritis (7.8 (4.4) v 8.6 (5.3); p>0.05 and 0.45 (0.23) v 0.48 (0.26); p>0.05, respectively). Conclusions: Leptin production per unit of fat mass is similar in patients and controls. The hypothesis that high levels of proinflammatory cytokines that characterise JIA might induce an increase of adipocytes leptin production is not supported by the results. Leptin may be a marker of nutritional status of JIA.